Factors Associated with the Incidence of Dengue Hemorrhagic Fever (DHF) at the Suruh Trenggalek Health Center - Tri Adi Putra; Agusta Dian Ellina (PT. Griya Eka Sejahtera, 2020)
Background: Dengue Hemorrhagic Fever (DHF) is one of the public health problems in Indonesia which tends to increase in the number of patients and the wider its spread. The purpose of this study was to determine the factors for the occurrence of Dengue Hemorrhagic Fever (DHF) in the Public Health Center in Suruh Trenggalek. Method: The research design used is quantitative with a